Bentuk Apresiasi Guru Terhadap Siswa Dalam Memotivasi Belajar Seni Tari Di SMK Negeri 9 Padang - Siti Khodijah; Indrayuda Indrayuda (Institut Nalanda, 2023)
This study aims to analyze and describe the form of teacher appreciation for students in motivating dance learning at SMK Negeri 9 Padang. This type of research is qualitative research with a descriptive approach. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data were collected through observation, interviews, documentation and literature study. The steps of analyzing data are collecting data, analyzing data and describing data. The results showed that giving teacher appreciation to students was very influential in an effort to motivate students in learning dance. Teachers play an important role in efforts to motivate students to learn dance. With the appreciation of students can make students motivated to learn dance. This can increase students' extrinsic motivation. With the increase in extrinsic motivation, students will be enthusiastic in learning dance because they feel that the slightest effort made will be appreciated by the teacher, so that students will get used to doing their obligations, meaning that students' intrinsic motivation will increase as well.